PERFORMANCE ANALYSIS USING CODE CONVERTER APPROACH AND THE APPLICATION OF APPROXIMATE ENTROPY AS POST CLASSIFIER FOR THE CLASSIFICATION OF EPILEPSY RISK LEVELS FROM EEG SIGNALS - R, Harikumar; KUMAR P, SUNIL (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The electroencephalogram (EEG) is actually a measure of the cumulative firing of neurons in various parts of the brain. The EEG contains the information with regard to the changes in the electrical potential of the brain which is obtained from a set of recording electrodes. The aim of this paper is to give a performance analysis by considering the advantage of Code Converter technique and Approximated Entropy (ApEn) is used as a post classifier for the classification of the epilepsy risk levels obtained from EEG signals. Methods: The Data Acquisition of EEG signals are done initially from the hospital. Then the code converter approach is presented, as working on definite alphabets is much easier when compared to that of working on numericals. Finally, ApEn is used as a Post Classifier for the classification of epilepsy risk levels from EEG signals. Results: The Performance Index and Quality Values are the two important parameters that are used to assess the performance of the Code Converters and the Classifier. The Perfect Classification rate of 83.94% is achieved along with an Accuracy of 91.97% and a Quality Value of 18.5. Conclusion: The computation of this procedure seems to be very simple and versatile. Future works may use different Dimensionality Reduction techniques to analyze its performance with Approximated Entropy as Post Classifier. Keywords: Electroencephalogram signals, Code converter, Performance index, Quality values.